The Debtor’s Liability For The Loading Of Personal Security In Indonesia - Anggraeni, RR. Dewi; Imanuddin, Iman; Purmanto, Purmanto (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
This study aims to find out the legal liability as well as the judge’s consideration of personal guarantees in the case of debtors who are declared bankrupt based on act number 37/2004.. The research method used is the normative juridical method, using library data. The results of this study indicate that in personal guarantee liability, there are two different agreements but closely related to each other, namely the guaranteed principal agreement and the personal guarantee agreement as a guarantee of the main agreement. In the personal guarantee agreement, besides the main agreement, there is also an accessory agreement where a personal guarantee serves the obligations. Personal guarantee in this bankruptcy case is the debtor from the obligation to pay off the debt. The personal guarantee assets will only be used to the return of the debts to creditors when the property has been confiscated and auctioned. However, the proceeds are not sufficient to pay the debt. This could be due to the debtor having two or more creditors and not paid off at least one overdue debt and can be collected.